Response of the Martian ionosphere to solar activity including SEPs and ICMEs in a two-week period starting on 25 February 2015. (1st October 2017) - Duru, F.; Gurnett, D.A.; Morgan, D.D.; Halekas, J.; Frahm, R.A.; Lundin, R.; Dejong, W.; Ertl, C.; Venable, A.; Wilkinson, C.; Fraenz, M.; Nemec, F.; et al.
Abstract: In a two-week period between February and March of 2015, a series of interplanetary coronal mass ejections (ICMEs) and solar energetic particle (SEP) events encountered Mars. The interactions were observed by several spacecraft, including Mars Express (MEX), Mars Atmosphere and Volatile Evolution Mission (MAVEN), and Mars Odyssey (MO). The ICME disturbances were characterized by an increase in ion speed, plasma temperature, magnetic field magnitude, and energetic electron flux. Furthermore, increased solar wind density and speeds, as well as unusually high local electron densities and high flow velocities were detected on the nightside at high altitudes during the March 8 event. These effects are thought to be due to the transport of ionospheric plasma away from Mars. In the deep nightside, the peak ionospheric electron density at the periapsis of MEX shows a substantial increase, reaching number densities about 2.7 × 10 4 cm −3 during the second ICME in the deep nightside. This corresponds to an increase in the MO High-Energy Neutron Detector flux suggesting an increase in the ionization of the neutral atmosphere due to the high intensity of charged particles. Measurements of the SEP fluxs show a substantial enhancement before the shock of a fourth ICME causing impact ionization and absorption of the surface echo intensity which drops to the noise levels, below 10 −15 V 2 m −2 Hz −1 from values of about 2 × 10 −14 V 2 m −2 Hz −1 . Moreover, the peak ionospheric density exhibits a discrete enhancement over a period of about 30 h around the same location, which may be due to impact ionization. Ion escape rates at this time are estimated to be in the order of 10 25 to 10 26 s −1 . Highlights: An investigation of the ionosphere and solar wind environment of Mars during a high solar activity period is provided. Solar energetic particles, high ionospheric densities and absorption of the surface intensity are observed on the nightside. ICMEs increase the ion escape rates. A top-hat feature in the peak electron density is observed.